Analisis Kelayakan Ekonomi Koagulan Biji Kelor dalam Menurunkan Konsentrasi Parameter Limbah Cair Tahu - Sinaga, Ruth Stefanie; Adzillah, Wilma Nurrul; Mentari, Okti Dinasakti Nurul (Jurnal Teknologi Lingkungan Lahan Basah, 2025)
The tofu industry in Karawang Regency produces liquid waste with high BOD, COD, and TSS content that can pollute the environment. The study aims to test the effectiveness of moringa seeds (Moringa oleifera) as a natural coagulant in reducing these pollutant parameters and to assess its economic feasibility. The method used involved laboratory testing with coagulation-flocculation processes using varying doses of moringa seed powder (11g, 13g, 15g, and 17g), followed by analysis of BOD, COD, and TSS. Financial viability was analyzed using the NPV, IRR, and Net B/C Ratio indicators. The results showed that a dose of 13 grams reduced COD by 57.51% and BOD by 34.63%, while TSS decreased by 59.06% at a dose of 11 grams. Financial analysis indicates that the use of moringa seeds as a coagulant is feasible with an NPV of Rp5,754,422, an IRR of 13.75%, and a Net B/C Ratio of 1.09. Thus, moringa seeds have proven to be effective and economical as a natural coagulant in soybean curd wastewater treatment and can serve as an environmentally friendly alternative for small-scale industries.